Pengaruh Pembelajaran Pendidikan Agama Islam Berbasis Higher Order Thinking Skill (HOTS) terhadap Sikap Berpikir Kritis Siswa - Lilawati, Emi; Pertiwi, Widya; Wardani, Dian Kusuma (ISLAMIKA, 2024)
This study is conducted in the context of the expectation that graduates of today's curricula would possess advanced critical thinking abilities. Indonesia is attempting to address this by putting HOTS-based learning into practice. As a matter of fact, not all educational institutions have successfully incorporated High Order Thinking Skills (HOTS) as high-level/critical thinking skills due to a number of factors, including the availability of both natural and human resources at various levels and institutions. Therefore, this study aims to determine students' critical thinking skills in learning Islamic Religious Education and to determine the effect of Islamic Religious Education learning based on Higher Order Thinking Skills (HOTS) on students' critical thinking attitudes in Class X SMA PGRI 1 Jombang. This study uses a quantitative type methodology with data instruments through the provision of tests and questionnaires. in class X SMA PGRI 1 Jombang, with a total study population of 310 students and a sample of 72 students. Data analysis techniques in this study include descriptive analysis, classical assumptions include data normality tests, homogeneity tests, linearity tests and measuring hypotheses with a simple linear regression test. The results of this study can be concluded that the critical attitude ability of SMA PGRI 1 Jombang in Islamic Religious Education subjects is in the High category because it has an average score of 77.27. there is a significant influence between HOTS Islamic Religious Education Learning and the critical attitude of SMA PGRI 1 Jombang students, due to data analysis from the test results of the calculation coefficient of determination R = 0.332 and R² = 0.110. It can be interpreted that social support plays a role in resilience by 11% and the rest are other variables not mentioned in this study.